Temporal course of vascular response after fluoropolymer paclitaxel-eluting stent implantation for femoropopliteal artery lesions. (14th October 2021) - Tomoi, Y; Kuramitsu, S; Hiramori, S; Soga, Y; Ando, K
Abstract: Background: Limited data is available regarding the vascular response after fluoropolymer paclitaxel-eluting stent (FP-PES) implantation. We sought to assess the vascular response at 6- and 12-month after FP-PES implantation for femoropopliteal artery lesions using serial optical coherence tomography (OCT) examination. Methods and results: From the IMPERIAL trial, this study evaluated 10 de novo femoropopliteal lesions treated with FP-PES. The primary study endpoint was neointimal tissue coverage at 6- and 12-month follow-up as assessed by serial OCT examination. The incidence of peri-strut low-intensity area (PLIA) and extra-stent lumen (ESL) was also assessed. A total of 203 matched cross-sectional images were evaluated at 6- and 12-month (5, 615 and 5, 763 struts, respectively). From 6 to 12 months, the mean neointimal thickness tended to increase from 198 μm to 233 μm with a significant reduction in the incidence of malapposed struts (0.59% vs. 0.28%, p=0.039). Conversely, uncovered struts and PLIA were more frequently observed at 12 months (4.4% vs. 7.8%, p=0.01; 12.7% vs. 21.0%, p<0.001, respectively). The ESL area significantly increased over time without any difference in its incidence (0.24±0.32 mm 2 vs. 0.38±0.36 mm 2, p=0.009). Conclusions: Neointimal proliferation was markedly inhibited from 6 to 12 months after FP-PES implantation, whereas the incidence of uncovered struts and PLIA significantly increased over time with the enlargement of ESL. Funding Acknowledgement: Type of funding sources: None.